Meningkatan Kinerja Sumber Daya Manusia Melalui Lingkungan Kerja, Motivasi, Kompensasi - J, Jumawan; Aliyanti, Teti; Devianti, Faysa Firli; Puspita, Ayu Diah; Wijaya, Willy Jovadi; Setiawan, Agung (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This journal analyzes the influence of the work environment, motivation and compensation on increasing the capabilities of existing human resources. Motivation has a very important role in improving performance and can reduce absenteeism. Low morale is a characteristic of the lack of motivation felt by most employees. A pleasant work environment is also very important for employees. The more pleasant the work environment, the more enthusiastic employees will be about their work. For many companies, compensation is a key factor and concern in retaining and attracting quality employees.